One new species, two generic synonyms and eight new records of Thripidae from China (Thysanoptera) - Zhang, Shimeng; Wang, Zhaohong; Li, Yajin; Mound, Laurence (Zootaxa, 2018)
Baliothrips sunae sp.n. is described from eastern China, and eight thripid species are newly recorded from China. One species is shared with Europe, three with Australia and four with southeast Asia. Chilothrips Hood is synonymized with Oxythrips Uzel, and Graminothrips Zhang & Tong is synonymized with Organothrips Hood.